Exploring Consumers Subconscious Response On Marketing Mix Towards Green And Non-green Products A Neuromarketing Approach - Mansor, Aida Azlina (2019)
Marketing is the core of a business and the primary goal of marketing is to bring the products to the target market. Traditional products characteristics such as Product, Price, Promotion and Place are the most important attributes when consumers consider when making a purchase decision. However, one of the main reasons of some marketing strategy fail is because the inability to understand the decision making process that takes place in consumers’ subconscious minds. Thus, marketers waste most of their budget by attracting only 10% of the brain that drives consumers’ decisions. For that reason, a suitable method is therefore essential for marketers to understand the underlying responses when consumers make decision. Due to the issue, in the last few decades, significant advancement of neuroscience has resulted in the emergence of neuromarketing, which provides a better understanding of how subconscious minds reacts in everyday situations, especially in marketing activities. This new concept brings powerful insights and techniques into marketing research especially on consumers’ behaviour analysis. In this view, this study looks at the growing field of neuromarketing and aims to explore consumers’ subconscious minds by examining the effectiveness of marketing mix on consumers’ decision making process. This study employed Electroencephalograms (EEG) and Eye Trackers to examine consumers’ subconscious minds towards the main component of the marketing mix during the decision making process. A laboratory experiment employed thirty-one volunteers to take part in the study